Genetic encoding of a bicyclo[6.1.0]nonyne-charged amino acid enables fast cellular protein imaging by metal-free ligation - Borrmann, Annika; Milles, Sigrid; Plass, Tilman; Dommerholt, Jan; Verkade, Jorge M. M.; Wießler, Manfred; Schultz, Carsten; Hest, Jan C. M. van; Delft, Floris L. van; Lemke, Edward A. (ChemBioChem, 2012)
Visualizing biomolecules by fluorescent tagging is a powerful method for studying their behaviour and function inside cells. We prepared and genetically encoded an unnatural amino acid (UAA) that features a bicyclononyne moiety. This UAA offered exceptional reactivity in strain-promoted azide-alkyne cycloadditions. Kinetic measurements revealed that the UAA reacted also remarkably fast in the inverse-electron-demand Diels-Alder cycloaddition with tetrazine-conjugated dyes. Genetic encoding of the new UAA inside mammalian cells and its subsequent selective labeling at low dye concentrations demonstrate the usefulness of the new amino acid for future imaging studies.